2021
DOI: 10.1002/chir.23347
|View full text |Cite
|
Sign up to set email alerts
|

Enantiopure cryptophane derivatives: Synthesis and chiroptical properties

Abstract: This review addresses the synthesis of enantiopure cryptophane and the study of their chiroptical properties. Cryptophane derivatives represent an important class of macrocyclic compounds that can bind a large range of species in solution under different conditions. The overwhelming majority of these host molecules is chiral, and their chiroptical properties have been thoroughly investigated. The first part of this review is dedicated to the optical resolution and the synthesis of enantiopure cryptophane deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 125 publications
0
14
0
Order By: Relevance
“…Before applying the ECM, it is thus compulsory to know or study the exact orientation of the TDM. The classic study by Collet and Gottarelli on C 3 ‐cyclotriveratrylenes ( 3 , Figure 4) demonstrated the dependence of ECD spectra on the nature of ring substituents 66,67 . The sign of the exciton couplets observed in correspondence with 1 L a and 1 L b transitions of the benzene chromophores is dictated by the orientation of the TDMs, which ultimately depends on X and Y.…”
Section: Overview Of Selected Ecm Applicationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Before applying the ECM, it is thus compulsory to know or study the exact orientation of the TDM. The classic study by Collet and Gottarelli on C 3 ‐cyclotriveratrylenes ( 3 , Figure 4) demonstrated the dependence of ECD spectra on the nature of ring substituents 66,67 . The sign of the exciton couplets observed in correspondence with 1 L a and 1 L b transitions of the benzene chromophores is dictated by the orientation of the TDMs, which ultimately depends on X and Y.…”
Section: Overview Of Selected Ecm Applicationsmentioning
confidence: 93%
“…Blue double arrows represent the possible orientation of transition dipole moment according to the related effective symmetry, whose "shape" is suggested by red frames; the main symmetry elements are indicated by dotted lines and curved arrows Gottarelli on C 3 -cyclotriveratrylenes (3, Figure 4) demonstrated the dependence of ECD spectra on the nature of ring substituents. 66,67 The sign of the exciton couplets observed in correspondence with 1 L a and 1 L b transitions of the benzene chromophores is dictated by the orientation of the TDMs, which ultimately depends on X and Y. As an example, with Y=OMe, the 1 L b couplet is positive for X = OH and negative for X = OAc.…”
Section: Benzene Derivatives With Different Substitution Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chiroptical aspects of cryptophanes have been extensively reviewed by Baydoun and Brotin. [12] CTB units can exist in crown or saddle conformations (Figure 1a). [13] Consequently, cryptophanes can have globular or imploded conformations (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…The syn‐ and anti‐ diastereomers of cryptophanes tend to differ in their physico‐chemical and complexation properties. The chiroptical aspects of cryptophanes have been extensively reviewed by Baydoun and Brotin [12] …”
Section: Introductionmentioning
confidence: 99%